2012
DOI: 10.3354/meps09952
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent effects of an introduced oyster, Crassostrea gigas, on a native intertidal seagrass, Zostera marina 

Abstract: Seagrasses and bivalves co-occur worldwide, and each plays a role in the structure, function, and services of coastal ecosystems. While seagrasses are declining, bivalve aquaculture is expanding, and impacts from culture practices, as opposed to the cultured organisms themselves, need to be distinguished. In 2 experiments, we tested the effects of live Crassostrea gigas, an introduced oyster, on Zostera marina, a native seagrass, in Willapa Bay, Washington. Expt 1 involved adult oyster addition across a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Similarly, by fertilizing porewaters, tulip mussels (Modiolus americanus) can improve turtlegrass (Thalassia testudinum) leaf nutrient condition (Peterson and Heck, 1999) and growth (Peterson and Heck, 2001a,b). However, other studies have shown that enhancement of porewater ammonium by blue mussels, geoduck clams (Panopea generosa), and cultured oysters (Crassostrea gigas) does not affect eelgrass leaf nitrogen or growth (Worm and Reusch, 2000;Ruesink and Rowell, 2012;Wagner et al, 2012), despite low ambient nutrient concentrations (b30, b 100, and b20 μmol NH 4 + [L porewater] − 1 , respectively).…”
Section: Context-dependent Effects Of Bivalves On Seagrassesmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, by fertilizing porewaters, tulip mussels (Modiolus americanus) can improve turtlegrass (Thalassia testudinum) leaf nutrient condition (Peterson and Heck, 1999) and growth (Peterson and Heck, 2001a,b). However, other studies have shown that enhancement of porewater ammonium by blue mussels, geoduck clams (Panopea generosa), and cultured oysters (Crassostrea gigas) does not affect eelgrass leaf nitrogen or growth (Worm and Reusch, 2000;Ruesink and Rowell, 2012;Wagner et al, 2012), despite low ambient nutrient concentrations (b30, b 100, and b20 μmol NH 4 + [L porewater] − 1 , respectively).…”
Section: Context-dependent Effects Of Bivalves On Seagrassesmentioning
confidence: 96%
“…However, other studies have shown that sediment enrichment by mussels can inhibit the growth of seagrasses by increasing concentrations of toxic sulfides Vinther et al, 2012). In other instances, bivalves may have mixed (Reusch and Williams, 1998) or no (e.g., Worm and Reusch, 2000;Wagner et al, 2012) effects on seagrass growth. These variable and inconsistent effects cannot be satisfactorily explained by nutrient availability, suggesting more complex interactions.…”
Section: Introductionmentioning
confidence: 95%
“…It is unknown whether filter-feeding molluscs may reduce concentrations of LZ in the water column, or if this process may be compromised at high pCO 2 . Many species of oysters, including Pacific oysters, frequently co-occur with eelgrass, either in naturalized populations or in aquaculture (Wall et al 2008, Wagner et al 2012 making them an obvious candidate for investigating this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Wagner et al (2012) showed that competition for space between oysters and seagrass did not follow a 1:1 relationship and a threshold of about 20% shell cover existed, above which Z. marina density declined exponentially, at least at small experimental scales. With the exception of areas where oysters are allowed to form reefs or hummocks near the south end of Willapa Bay, however, cultured oyster density rarely reaches this threshold , 2011, Tallis et al 2009, and eelgrass commonly co-exists with oysters throughout the growout cycle, albeit at reduced density.…”
Section: Oyster Culture Bed Typementioning
confidence: 96%